Semiconductor film preparation method based on nano material
Through the composite material of graphene, MoS2 and quantum dots, combined with electric field modulation and low-temperature annealing treatment, the problem of low electron transmission and photoelectric conversion efficiency of existing semiconductor thin film materials was solved, and the preparation of high-performance and stable thin films was achieved.
Patent Information
- Application Number
- CN202510979014.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-09-30
AI Technical Summary
Existing semiconductor thin film materials have problems such as low electron transmission efficiency, unstable photoelectric conversion efficiency and performance degradation after long-term use. Especially when using a single material or simple composite materials, there are problems such as poor interface compatibility, insufficient film stability and complex processing technology.
A composite material of graphene, transition metal disulfide (MoS2) and quantum dots is used to form a thin film by spin coating or spray coating, and an external electric field is applied for modulation, combined with low-temperature annealing treatment to optimize the electron migration path and film performance.
It significantly improves the electron mobility and photoelectric conversion efficiency of semiconductor films, simplifies the process flow, and improves the response speed and stability of materials, making it suitable for high-performance optoelectronic devices.
Smart Images

Figure CN120730869A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor materials, and in particular to a method for preparing a semiconductor thin film based on nanomaterials. Background Art
[0002] With the rapid development of electronic technology, demand for optoelectronic devices, solar cells, and photoelectric sensors continues to increase, placing particular demands on materials that are efficient, stable, and flexible. In recent years, nanomaterials, owing to their unique electronic, optical, and mechanical properties, have become a key research area for semiconductor thin-film materials. Graphene, transition metal dichalcogenides (MoS2), and quantum dot materials, in particular, have demonstrated broad application prospects in optoelectronic devices, sensors, and energy storage due to their excellent conductivity, optoelectronic properties, and tunability.
[0003] Most existing semiconductor thin film materials are based on a single material. Although traditional materials such as silicon-based semiconductors are widely used in electronic devices, their performance has certain limitations. For example, silicon materials have a narrow light absorption range and low electron mobility, and their application in flexible electronic devices is restricted by the rigidity of the material itself. In recent years, researchers have tried to use two-dimensional materials or composite materials such as graphene, MoS2, and quantum dots to improve the conductivity and photoelectric conversion efficiency of thin films. Although these new materials have good photoelectric properties and conductivity, they still have problems such as poor interface compatibility between materials, insufficient film stability, and complex processing technology, which makes it difficult for them to meet the requirements of high performance, high stability, and low cost in practical applications.
[0004] Existing thin film materials, particularly nanomaterial-based composite films, suffer from low electron transfer efficiency, unstable photoelectric conversion efficiency, and performance degradation over time. In particular, when using single materials or simple composite materials, the lack of effective electron migration pathway optimization and surface modification results in slow photoelectric response and poor stability under varying environmental conditions. Therefore, improving the performance of nanomaterial composites, particularly in terms of electron migration and photoelectric conversion efficiency, through improved thin film preparation processes has become a pressing challenge in current technology. Summary of the Invention
[0005] In view of the deficiencies of the prior art, the present invention provides a method for preparing a semiconductor thin film based on nanomaterials, which solves the deficiencies of the thin film materials in the prior art in terms of electron transport, photoelectric response and stability.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing a semiconductor thin film based on nanomaterials, comprising the following steps: Step 1: preparing graphene, transition metal disulfide material and quantum dots, and mixing them in a predetermined ratio to form a composite solution; Step 2: coating the composite solution onto a substrate to form a thin film by spin coating, spray coating or dip coating; Step 3: Applying an external electric field to the coated film for modulation to optimize the electron migration path; Step 4: performing low temperature annealing treatment; Step 5: Obtain a semiconductor film with high electron mobility and good photoelectric conversion performance.
[0007] Preferably, the components in the composite solution are mixed in the following weight proportions: 10%-30% graphene, 20%-40% MoS2, 5%-15% quantum dots, 20%-50% alumina, 1%-10% organic solvent, and 0.5%-2% interface modifier.
[0008] Preferably, the quantum dots are CdSe, PbS or a mixture thereof, and the particle size of the quantum dots is in the range of 3-10 nm.
[0009] Preferably, the substrate is an aluminum oxide substrate, the thickness of the thin film deposition is 50-500 nm, and the surface of the substrate is plasma treated.
[0010] Preferably, the spin coating method has a spin coating rate of 1500-3000 rpm, a spin coating time of 30-60 seconds, and an ambient temperature during the coating process of 20-25°C.
[0011] Preferably, the electric field modulation step includes applying an electric field with an electric field strength of 1-10 V / cm, and the electric field modulation time is 5-30 minutes.
[0012] Preferably, the annealing temperature is 250-400° C., the annealing time is 30-60 minutes, and the atmosphere during the annealing process is nitrogen protection.
[0013] Preferably, the thin film coated on the substrate is deposited by spraying, with a spraying distance of 15-30 cm, a spraying speed of 1-5 m / s, and a spraying thickness controlled at 50-500 nm.
[0014] Preferably, the graphene in the composite solution is synthesized by chemical vapor deposition or reduced graphene oxide method, MoS2 is synthesized by CVD method, and the quantum dots are synthesized by solution method, and the particle size can be controlled by adjusting the solvent, temperature and reaction time.
[0015] Preferably, the electric field modulation step is performed by an electric field assisted deposition device, the electric field intensity ranges from 1 to 10 V / cm, the electric field application time is from 5 to 30 minutes, and the electric field direction is parallel to the thin film deposition direction.
[0016] The present invention provides a method for preparing a semiconductor thin film based on nanomaterials. It has the following beneficial effects: 1. This invention utilizes a nanomaterial-based semiconductor thin film preparation method, combining graphene, MoS2, and quantum dots to optimize the film's conductivity and photoelectric properties, significantly improving electron mobility and photoelectric conversion efficiency. Compared to existing semiconductor thin films made from a single material, this method overcomes limitations in electron transport and light absorption, significantly enhancing the material's overall performance.
[0017] 2. This invention optimizes the electron migration pathways within the thin film through electric field modulation, effectively reducing electron recombination and improving the film's photoelectric conversion efficiency. Compared to traditional annealing and chemical treatment techniques, this method eliminates the need for complex post-processing steps, simplifies the process flow, and significantly improves the material's response speed and stability, making it particularly suitable for high-performance optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Flowchart of the present invention. DETAILED DESCRIPTION
[0019] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the present specification. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0020] Please see the attached Figure 1 The present invention provides a method for preparing a semiconductor thin film based on nanomaterials, comprising the following steps: Step S1: Preparation and mixing of nanomaterials In the overall preparation method of the present invention, step S1 involves the selection, preparation, and mixing of nanomaterials. To ensure that the final film's performance meets the desired targets, the material selection and mixing ratio must be strictly controlled, which in turn affects the subsequent film's conductivity, photoelectric conversion efficiency, and stability. Proper implementation of this step lays the foundation for the success of the entire preparation process.
[0021] In this embodiment, in step S1, graphene, transition metal dichalcogenides (TMDs), and quantum dots are first selected and prepared. These nanomaterials are chosen based on their excellent properties in electron transport and photoelectric conversion, ensuring that the film has excellent performance.
[0022] Graphene, a highly conductive two-dimensional material, possesses extremely high electron mobility, making it crucial for the fabrication of high-performance semiconductor films. The interlayer spacing and surface structure of graphene provide efficient electron transport pathways. Specifically, in this embodiment, the graphene mass fraction is controlled between 10% and 30% (by weight). This ratio ensures that the film maintains sufficient electronic conductivity while still performing well in photoelectric conversion.
[0023] Transition metal dichalcogenides (TMDs), such as MoS2, are two-dimensional materials with tunable band gaps. They possess excellent light absorption and electrical conductivity, making them particularly suitable for use in semiconductor thin films. The band gap of MoS2 can be adjusted based on the number of layers, offering significant advantages in improving photoelectric conversion efficiency. The mass fraction of MoS2 is typically set at 20%-40%, a ratio that effectively modulates the band gap of the film while also enhancing photoelectric conversion efficiency.
[0024] Quantum dots, such as CdSe and PbS, play a crucial role in photoelectric conversion by precisely adjusting their particle size to control their optical absorption properties. The inclusion of quantum dots enables thin films to absorb a wider range of light, from ultraviolet to visible light. The mass fraction of quantum dots is typically controlled between 5% and 15%, ensuring enhanced light absorption without negatively impacting electrical conductivity.
[0025] In this embodiment, the mixing of the nanomaterials needs to ensure that the components are evenly distributed, thereby ensuring the uniformity and consistency of the composite film. To achieve this goal, a suitable solvent such as NMP or DMF is used as the dispersion medium. Specifically, the mass fraction of the solvent can be adjusted to 1%-10% to ensure that the nanomaterials are fully dispersed and do not aggregate.
[0026] The addition of an interface modifier is to improve the interfacial bonding between graphene and MoS2, enhance the migration efficiency of electrons, and avoid the problem of electron recombination caused by interface instability. The mass fraction of the interface modifier is usually controlled at 0.5%-2%. Specifically, in this embodiment, it is recommended to use phenyl phosphate as a modifier, which can promote the good combination of the two two-dimensional materials through electrostatic interaction and chemical modification.
[0027] In some embodiments, ultrasonic dispersion technology can be used during the mixing process to improve the uniformity of nanomaterial dispersion. Ultrasonic waves can effectively break up the nanomaterials, preventing uneven distribution caused by agglomeration. The dispersion process is typically controlled to last between 30 and 60 minutes to ensure sufficient and stable dispersion.
[0028] In one possible implementation, after the nanomaterials are mixed, the composite solution can be allowed to stand or be stirred at low speed to remove bubbles and ensure stability and uniformity. The viscosity of the mixed solution is typically controlled between 1 and 2 Pa·s, which ensures the solution is suitable for coating processes such as spin coating or spray coating, and avoids excessively thick or thin solutions that could affect film quality.
[0029] The resulting composite solution not only exhibits excellent uniformity and stability, but also forms a uniform and dense film during the next coating process. The successful completion of this step provides a solid foundation for subsequent film preparation, ensuring controllable and superior film performance.
[0030] By optimizing and implementing step S1, the present invention can significantly improve the conductivity, photoelectric conversion efficiency, and stability of the composite film. The reasonable proportion and good dispersion of graphene, MoS2, and quantum dots ensure the high efficiency of the film material. In addition, the introduction of the interface modifier solves the interface problem between the materials, effectively reduces the recombination phenomenon of carriers, and further optimizes the electron migration path. Ultimately, the obtained semiconductor film has good electronic performance, photoelectric conversion efficiency, and mechanical stability in practical applications, and is suitable for various fields such as solar cells, photoelectric sensors, and flexible electronics.
[0031] Step S2: Thin film coating In the present invention, step S2 involves coating the composite solution onto a substrate to form a uniform semiconductor thin film. The quality of the thin film is closely related to the coating process. Therefore, this step requires precise control of solution distribution, substrate preparation, coating method, and process parameters to ensure that the resulting thin film possesses the desired properties, particularly in terms of electron migration and photoelectric conversion.
[0032] In this embodiment, in step S2, the composite solution is applied to the substrate surface via spin coating, spray coating, or dip coating. The specific coating method chosen depends on the substrate material and the desired film thickness and uniformity requirements. In this embodiment, spin coating was selected because it is suitable for rapid and uniform coating of large-area thin films and is easy to control film thickness.
[0033] Generally speaking, substrate selection is crucial for thin film formation. Common substrate materials include glass, silicon wafers, and aluminum oxide (Al2O3). The surfaces of these substrates often require pretreatment to enhance film adhesion. Substrate cleanliness directly impacts film quality, so prior to coating, the substrate should be cleaned, typically using chemical or ultrasonic cleaning to remove surface dirt and grease.
[0034] In this embodiment, plasma treatment is used to treat the substrate surface, making it more hydrophilic or oleophilic, thereby improving the adhesion of the coated film. Common plasma treatment conditions include nitrogen or oxygen in the atmosphere, a treatment time of 10-30 seconds, and a power of 50-150W.
[0035] The configuration of the composite solution during the coating process also requires precise control. The ratio of graphene, MoS2, and quantum dots in the composite solution significantly influences the film's performance. Therefore, the solution concentration needs to be adjusted within a range of 1%-10% (by weight) to ensure the appropriate viscosity for spin coating or other coating methods.
[0036] Specifically, the composite solution is dispersed ultrasonically before coating to ensure uniform distribution of the components. Ultrasonic treatment typically lasts 30-60 minutes at a frequency of 20-40 kHz. This process effectively prevents nanomaterial agglomeration and ensures the stability of the nanoparticles in solution.
[0037] In this embodiment, spin coating was selected for film coating. During the spin coating process, the composite solution was added dropwise to a clean substrate, and then the substrate was rotated by a spin coater. The rate and time of spin coating were controlled between 1500-3000 rpm, and the spin coating time was usually set to 30-60 seconds. The spin coating rate affects the thickness of the film. A higher spin coating rate will make the film thinner, while a lower spin coating rate will result in a thicker film. Depending on the performance of the desired film, appropriately adjusting the spin coating parameters can obtain the desired film thickness. The final thickness of the film is usually controlled within the range of 50-500 nm. This thickness range helps to ensure the optimal performance of the film in terms of photoelectric conversion and electron transport.
[0038] As an option, after coating, a low-temperature treatment can be used to further remove the solvent and enhance the film's stability. Typically, low-temperature drying is performed at a temperature of 60-80°C for 30-60 minutes. This helps maintain the film's structural stability and reduces damage that can occur with high-temperature treatment.
[0039] Specifically, in some embodiments, the coated film requires a debubbling treatment under a vacuum environment to prevent bubbles and uneven thickness during the coating process. The vacuum debubbling treatment typically requires a vacuum level of 0.1-1 Pa for 10-30 minutes. This debubbling process effectively removes excess bubbles from the film, ensuring excellent film uniformity and density.
[0040] In one possible implementation, if the film is uneven after coating, it can be improved by increasing the viscosity of the solution or adjusting the spin coating speed. By further optimizing the solution ratio and spin coating process parameters, the uniformity of the film can be ensured, avoiding the situation where the film thickness is too thick or unevenly distributed. By implementing step S2, the present invention can achieve the coating of a semiconductor film with high uniformity and controllable thickness. The successful implementation of this step directly affects the conductivity, photoelectric conversion efficiency, and stability of the subsequent film. The precise spin coating process can ensure the thickness and uniformity of the film, avoiding current loss and unstable performance caused by uneven film. In addition, auxiliary steps such as plasma treatment and degassing treatment provide good adhesion and stability for the film, providing a solid foundation for subsequent electric field modulation and annealing treatment.
[0041] Step S3: Electric field modulation In the semiconductor thin film preparation process of the present invention, step S3 involves applying an external electric field to the formed thin film for modulation. Electric field modulation optimizes the migration path of carriers within the thin film through the action of an external electric field, thereby improving the film's electrical properties. Electron migration in thin films is limited by film thickness, grain distribution, and interface effects. Therefore, appropriate electric field modulation can not only reduce electron backflow and increase conductivity, but also effectively improve photoelectric performance.
[0042] In this embodiment, after the film coating is successfully completed in step S2, the electric field modulation stage is entered. The coated film is in a low-energy state to a certain extent, and the electron migration in the film is subject to a certain resistance. To optimize the migration path of electrons in the film and enhance the electron diffusion rate, an external electric field is applied to the film surface. This electric field promotes the migration of carriers along a specific direction, optimizing their distribution and mobility. This can effectively reduce carrier recombination and improve the diffusion efficiency of carriers in the film.
[0043] Generally, the electric field strength is controlled within the range of 1-10 V / cm. The electric field strength should be adjusted based on the film thickness, material properties, and target performance. For thin films, a low electric field strength may not be sufficient to effectively alter the carrier migration path, while an excessively strong electric field may disrupt the film's microstructure or cause unnecessary damage. By properly controlling the electric field strength, carriers can be given sufficient energy, thereby improving their diffusion rate within the film.
[0044] As an option, the electric field is typically applied for 5–30 minutes. This timeframe allows the electric field to fully affect the carriers in the film, altering their migration paths and diffusion rates. A shorter application time may result in a less pronounced electric field effect, while a longer application time may cause uneven carrier migration, impacting the film's ultimate performance. Therefore, the application time needs to be optimized based on the film's characteristics and the desired end result.
[0045] Specifically, when applying the electric field, the direction of the field should be parallel to the deposition direction of the film. This parallel electric field ensures that the direction of electron migration on the film surface is consistent with the structural orientation of the film, avoiding uneven electron flow caused by inconsistent electric field direction. In some cases, electric field-assisted deposition equipment can be used to precisely control the direction and intensity of the electric field to ensure accurate application of the electric field.
[0046] In one possible implementation, the temperature of the film can be appropriately adjusted when an electric field is applied. Temperature regulation helps to increase the activity of carriers and promote their migration speed. Specifically, the temperature can be controlled between 50°C and 100°C, and the electronic properties of the film can be further optimized by temperature regulation. Appropriate temperature treatment can not only accelerate electron migration, but also reduce the thermal stress that may be generated during the application of the electric field, thereby reducing material damage or defects caused by excessive temperature.
[0047] In some embodiments, an alternating electric field (AC) rather than a direct electric field (DC) can be introduced during the electric field modulation process. The introduction of an AC electric field can regulate the electron migration path in the film through periodic field reversals, preventing electrons from migrating in a single direction. This not only enhances electron diffusivity in the film but also reduces charge accumulation caused by excessive concentration of the electric field in a single direction, further improving the electrical stability of the film.
[0048] In another possible implementation, if the thin film has a multilayer or heterojunction structure, the application of the electric field can also be controlled by utilizing the electric field gradient between different layers. This gradient effect can more effectively promote the separation of electrons and holes, further improving the photoelectric conversion efficiency of the thin film, especially in applications such as solar cells and other optoelectronic devices.
[0049] By implementing electric field modulation, electron migration paths within the thin film are effectively optimized. This helps increase carrier migration speed within the film and reduce charge recombination caused by interface defects or material inhomogeneities. Applying an appropriate electric field can direct electron migration along efficient paths within the film, significantly improving the film's conductivity and photoelectric conversion efficiency.
[0050] Through the action of the electric field, the carriers can gain more kinetic energy, thereby increasing their mobility, which results in a significant improvement in the conductivity and optoelectronic properties of the film.
[0051] Electric field modulation can effectively separate electrons and holes, reducing carrier recombination in the film. This improves the efficiency of the film in the photoelectric conversion process, especially in solar cells, where it can significantly improve the conversion efficiency of the cell.
[0052] During the electric field modulation process, the distribution of electrons is more uniform, which helps to improve the overall performance of optoelectronic devices, especially in applications such as photoelectric sensors and flexible electronics.
[0053] Step S4: Annealing In the semiconductor thin film preparation process of the present invention, step S4 is a key annealing step, which plays an important role in optimizing the film's structure, improving its performance, and ensuring its stability. Annealing, by providing thermal energy, promotes the adjustment of the film material's crystal structure, reduces defect density, and improves its electrical conductivity, optoelectronic properties, and mechanical strength.
[0054] In this embodiment, after the electric field modulation is completed in step S3, the film already has certain electrical and optoelectronic properties. However, defects, lattice structure irregularities, and material impurities in the film may still affect its ultimate performance. Therefore, the goal of the annealing treatment is to improve these issues through thermal treatment, thereby optimizing the overall performance of the film.
[0055] Annealing conditions, such as temperature, duration, and atmosphere, have a decisive influence on the quality and performance of thin films. Annealing gradually removes excess energy from the material in the film under the influence of temperature fluctuations, promoting atomic or molecular rearrangement and reducing or eliminating lattice defects, thereby enhancing the film's conductivity, photoelectric conversion efficiency, and stability.
[0056] Generally, the annealing temperature range is usually controlled between 250-400°C. Lower temperatures cannot effectively promote the lattice rearrangement of the material, while too high a temperature may cause damage or deformation of the film. Therefore, the temperature setting should be optimized based on the characteristics of the film, the thermal stability of the film material, and the target performance. In this embodiment, the annealing temperature is set to 350°C. This temperature can effectively promote the rearrangement of the material lattice while avoiding the possible degradation or damage of the material at too high a temperature.
[0057] As an option, the annealing time is usually controlled at 30-60 minutes. A shorter annealing time may not be enough to fully optimize the film structure, while too long a time may lead to excessive heat treatment of the material, thereby causing the film performance to deteriorate. Therefore, the setting of the annealing time needs to comprehensively consider the thickness of the film, the material properties and the ultimate performance goals. In this embodiment, the annealing time is set to 45 minutes to ensure sufficient optimization of the crystal structure and avoid the negative effects of excessive annealing.
[0058] Specifically, the annealing process is usually carried out in an inert gas environment to prevent the film from oxidizing or reacting with oxygen in the air. Common protective atmospheres include nitrogen, argon, or other inert gases. In this embodiment, a nitrogen protective atmosphere is used, and the air flow rate is set at 50-100 mL / min to ensure that the film does not oxidize during the annealing process and maintain stable atmospheric conditions. The nitrogen flow can effectively remove the gases generated during the annealing process and maintain the stability of the film.
[0059] In one possible implementation, step-by-step annealing can also be considered during the annealing process. Step-by-step annealing refers to multiple annealing stages at different temperatures to optimize different physical properties of the film. For example, in the first stage, the temperature can be set to 300°C for 20 minutes to reduce defects in the initial annealing process; then, the temperature is raised to 350°C and annealed for 25 minutes to further optimize the crystal structure of the film and reduce defects or excessive grain growth that may occur during the high temperature process. This step-by-step annealing method can ensure that the film undergoes physical changes in a more stable and uniform manner during the annealing process.
[0060] In some embodiments, the annealing process can also utilize radiative heating, which offers advantages over traditional convection heating, such as uniform heating and faster temperature rise. Using infrared or laser heating devices to heat the film to the desired temperature in a shorter time can reduce thermal diffusion effects, ensure uniform heating of the film, and thus avoid damage to the film due to localized overheating.
[0061] Furthermore, the temperature ramp rate during the annealing process is also a critical parameter. Generally, the temperature ramp rate is typically controlled between 5°C / min and 20°C / min. A too rapid heating rate can cause excessive thermal stress in the film, resulting in uneven film surfaces or cracking, while a too slow heating rate can affect annealing efficiency. According to the requirements of this embodiment, the temperature ramp rate is set to 10°C / min, which ensures that the film does not experience excessive thermal stress or excessive temperature fluctuations during the heating process.
[0062] Step S5: Film surface modification and functionalization In the semiconductor thin film preparation process of the present invention, step S5 involves surface modification and functionalization of the annealed thin film. While annealing can optimize the film's electron transport and optoelectronic properties, the film's surface properties still significantly impact its overall performance. Surface modification and functionalization can further enhance the film's stability and interfacial adhesion, regulate its surface energy, and improve its application performance, particularly in optoelectronic devices.
[0063] In this embodiment, after the annealing treatment is completed in step S4, the film's microstructure is optimized, and the film then enters the surface modification and functionalization stage. The goal of this step is to introduce specific functional groups onto the film surface through chemical modification methods, thereby improving the bonding between the film and the substrate, adjusting the film's surface properties, and further enhancing its electrical, optical, and mechanical properties.
[0064] Typically, surface modification methods include introducing chemical groups, using self-assembled monolayer (SAM) technology, or functionalizing the interface by introducing small organic molecules and polymers. These methods can make the film surface more hydrophilic or oleophilic, thereby improving the contact quality between the film and other materials or substrates. Surface modification can also improve the environmental stability of the film in practical applications, preventing the effects of external factors such as moisture and oxygen on the film's performance.
[0065] Alternatively, in this embodiment, the film surface can be modified to enhance its surface activity by introducing functional groups (e.g., carboxyl (–COOH), amino (–NH2), phosphate, etc.). These functional groups can enhance the hydrophilicity or lipophilicity of the film surface, optimizing the film's adhesion to the substrate. Specifically, carboxyl (–COOH) groups can provide a strong surface hydrophilicity, thereby promoting the film's affinity for aqueous solutions, while amino (–NH2) groups can enhance its adhesion to certain metals or other materials.
[0066] Specifically, the film surface can be functionalized using solution dip coating or chemical vapor deposition (CVD). In the solution dip coating method, the film is immersed in a solution containing functional groups. After soaking for a certain period of time, the functional groups can react chemically with the film surface, forming a stable chemical bond. In the CVD method, the reaction gas grows a specific functionalized layer on the film surface through a gas phase reaction, further enhancing the film's stability and interfacial bonding strength.
[0067] In one possible implementation, to enhance the adhesion between the film and the substrate, phosphate groups (–PO4) can be introduced onto the film surface. These groups can form strong hydrogen bonds or coordination interactions at the interface between the film and the substrate, enhancing the binding force between the two. Specifically, the phosphate groups on the film surface form a strong bond with materials such as metal substrates and oxide substrates, ensuring the stability of the film during long-term use.
[0068] In some embodiments, surface modification and functionalization can also be achieved through self-assembled monolayer (SAM) technology. By self-assembling specific organic molecules on the film surface to form a molecular-level film, the interfacial stability and surface properties of the film can be effectively improved. The SAM method uses a solution method to introduce molecules with functional groups to the film surface, forming a monolayer molecular structure. This method not only adjusts the hydrophilicity or lipophilicity of the surface, but also introduces additional chemically active groups on the film surface, further improving the stability of the film in various environments.
[0069] Alternatively, functional materials can be deposited directly onto the film surface using external electric fields or chemical reactions through methods such as physical vapor deposition or electrochemical deposition, creating more complex surface modification layers. For example, a layer of conductive polymers or organic molecules can be electrochemically deposited onto the film surface to impart higher conductivity or improved surface adhesion.
[0070] In certain embodiments, surface modification can also involve polymer coating. By applying a thin layer of polymer to the film surface, the film's mechanical stability can be further enhanced, protecting it from environmental influences. The type of polymer layer can be selected as needed, such as polyvinyl alcohol (PVA) or polyurethane (PU). These materials not only improve the film's flexibility but also provide an additional layer of protection, extending its lifespan.
[0071] Example 1: Application of the semiconductor thin film preparation method based on nanomaterials in solar cells Background: Solar cells, a green, renewable energy source, have been widely used worldwide. However, the efficiency and stability of solar cells remain limited by material properties. In particular, existing solar cells experience significant performance degradation in high temperature, humidity, and after prolonged use, particularly in terms of photoelectric conversion efficiency and thin film stability. Therefore, improving the photoelectric conversion efficiency and long-term stability of solar cells remains a pressing technical challenge.
[0072] The goal of this embodiment is to use the nanomaterial-based semiconductor thin film preparation method of the present invention to optimize the performance of the photoelectric conversion material in the solar cell, especially to improve the electron mobility and photoelectric conversion efficiency of the film, thereby improving the overall performance of the solar cell.
[0073] Step S1: Preparation and mixing of nanomaterials First, a composite material consisting of graphene, MoS2 (transition metal dichalcogenides), and quantum dots (such as CdSe and PbS) was selected. Graphene provides high conductivity, MoS2 is used to adjust the band gap to enhance light absorption, and quantum dots help extend the light absorption range, particularly from the ultraviolet to the visible.
[0074] To prepare the composite solution, graphene, MoS2, and quantum dots are mixed in weight ratios of 10%-30%, 20%-40%, and 5%-15%, respectively. The solvent is NMP (N-Methyl-2-pyrrolidone), with a concentration of 5wt%. Ultrasonic dispersion is performed using an ultrasonic disperser to ensure uniform distribution of the components.
[0075] Step S2: Thin film coating The composite solution was applied to a clean transparent conductive oxide (TCO) substrate using spin coating. The substrate was a fluorine-doped zinc oxide (FTO) glass substrate, which had been plasma-treated to improve film adhesion. The spin coating speed was 2000 rpm and the coating time was 45 seconds to ensure uniform film thickness of 200 nm.
[0076] After coating, the film surface was air-dried for 1 hour to remove the solvent.
[0077] Step S3: Electric field modulation After the film coating is complete, the electric field modulation step begins. During this process, an electric field is applied via an electric field-assisted deposition device with a strength of 3 V / cm for 20 minutes. This electric field optimizes the electron migration path in the film, reduces electron-hole recombination, and improves photoelectric conversion efficiency.
[0078] To further improve electron transport in the film, the film was maintained at 60°C under the action of an electric field. The role of electric field modulation is to migrate electrons to the active area, reducing the poor electron transport caused by interface defects or molecular chain confinement.
[0079] Step S4: Annealing After the electric field modulation is complete, the film enters the annealing stage. The annealing temperature is set at 350°C for 45 minutes under a nitrogen atmosphere at a flow rate of 50 mL / min. Annealing removes residual solvent from the film, optimizes the material's lattice structure, and reduces defects and impurities, further improving the film's optoelectronic properties.
[0080] In this step, the lattice of the film is optimized by adjusting the temperature, which increases the migration path of electrons and holes and improves the conductivity and photoelectric conversion efficiency of the film.
[0081] Step S5: Surface modification and functionalization After the film annealing treatment, the surface modification and functionalization step begins. The film surface is immersed in a solution containing amino (–NH2) and carboxyl (–COOH) groups for functionalization. The immersion time is 30 minutes to ensure that the functional groups are evenly distributed across the film surface. These functional groups enhance the film's hydrophilicity and adhesion to the substrate, further reducing carrier recombination and improving photoelectric conversion efficiency.
[0082] At the same time, the film surface is treated by self-assembled monolayer (SAM) technology to further improve the film's interface stability and resistance to environmental degradation.
[0083] Solar cell assembly After the film surface modification is complete, it is used to construct the photovoltaic absorption layer of the solar cell. Using evaporation deposition technology, metal electrodes (such as silver or aluminum) are evaporated onto the film surface to form the positive and negative electrodes of the cell. Finally, the assembled solar cell is tested under external light to evaluate its photovoltaic conversion efficiency.
[0084] Example 2: Application of the Semiconductor Thin Film Preparation Method Based on Nanomaterials in Photoelectric Sensors Background: Photoelectric sensors are widely used in environmental monitoring, smart devices, security systems, and other fields. Their performance is directly influenced by the optoelectronic materials used. Traditional photoelectric sensors often use metal oxides or organic semiconductors, but these materials suffer from low photoelectric conversion efficiency and slow response speed. In recent years, nanomaterials, due to their excellent electrical and optical properties, have become an important material for improving the performance of photoelectric sensors. By using semiconductor thin films based on nanomaterials, the response speed and photoelectric conversion efficiency of sensors can be effectively improved.
[0085] The goal of this embodiment is to use a semiconductor thin film preparation method based on nanomaterials to optimize the performance of photoelectric sensors, especially in terms of improving their light response speed, photoelectric conversion efficiency and long-term stability, thereby improving the reliability and efficiency of the sensors in practical applications.
[0086] Step S1: Preparation and mixing of nanomaterials First, graphene, MoS2 (transition metal disulfide), and quantum dots (such as CdSe and PbS) were selected as the photoelectric absorption materials for the photosensor. Graphene has excellent electronic conductivity, while MoS2 has a tunable band gap, which helps enhance light absorption and electron separation. The addition of quantum dots can extend the material's light response range, particularly from ultraviolet to visible light.
[0087] To prepare the composite solution, graphene, MoS2, and quantum dots are mixed in weight ratios of 10%-30%, 20%-40%, and 5%-15%, respectively. NMP (N-Methyl-2-pyrrolidone) is used as the solvent at a concentration of 5wt%. Ultrasonic dispersion is performed using an ultrasonic disperser to ensure uniform distribution of the components and prevent agglomeration that could affect the material's performance.
[0088] Step S2: Thin film coating The composite solution is spin-coated onto a transparent conductive substrate (e.g., fluorine-doped zinc oxide (FTO) glass). During this step, ensuring film thickness and uniformity is crucial. The film thickness is typically controlled within the 200-300 nm range to ensure good photoelectric response. The spin coating speed is set at 2000 rpm for 45 seconds to ensure uniform film coating.
[0089] Step S3: Electric field modulation The coated film then enters the electric field modulation step. Electric field modulation optimizes electron migration pathways within the film through the application of an external electric field, helping to improve its electronic conductivity. This step is particularly crucial in photosensors, as it effectively reduces electron recombination and optimizes photoelectric conversion efficiency. The electric field strength is set at 3 V / cm and applied for 20 minutes.
[0090] The application of an electric field helps improve the separation efficiency of electrons and holes in the film, reducing carrier recombination and increasing the response speed of the photoelectric sensor. At the same time, the film is maintained at a temperature of 60°C, ensuring that the film's electron mobility and stability are further enhanced.
[0091] Step S4: Annealing Annealing is used to further optimize the film's lattice structure, reduce defects, and enhance its electrical conductivity and optoelectronic properties. Annealing temperature was set at 350°C for 45 minutes under a nitrogen atmosphere. The nitrogen flow rate was controlled at 50 mL / min to prevent oxidation during the annealing process.
[0092] The annealing process helps improve the film's electron mobility and reduce defect formation, enhancing the sensitivity and stability of the photosensor. Through this annealing step, the film's crystal structure is optimized, enhancing its mechanical strength and long-term stability, and reducing the performance degradation of the photosensor after long-term use.
[0093] Step S5: Surface modification and functionalization After annealing, the film enters the surface modification and functionalization stage. To improve the film's stability and response speed, the film surface is immersed in a solution containing amino (–NH2) and phosphate (–PO4) groups to ensure that the functional groups are evenly distributed across the film surface. These functional groups increase the film's surface hydrophilicity, improve adhesion to the substrate, and enhance the film's environmental stability during practical applications.
[0094] Through self-assembled monolayer (SAM) technology, a monolayer is formed on the film surface, further improving its interaction with the external environment. The functionalized film surface is more stable and has excellent resistance to environmental degradation, ensuring the long-term stable operation of the photoelectric sensor in complex environments.
[0095] Assembly of photoelectric sensors After surface modification and functionalization, the film is used as the photoelectric absorption layer of a photosensor. Metal electrodes (such as silver, aluminum, or gold) are evaporated and deposited on the film surface to form the positive and negative electrodes of the photosensor. The assembled photosensor is then tested for light response.
[0096] Example 3: Application of the semiconductor thin film preparation method based on nanomaterials in flexible electronic devices Background: With the rapid development of flexible electronic technology, products such as flexible displays and smart wearable devices have been widely used in the market. Flexible electronic devices, due to their lightness, thinness, and bendability, can adapt to more diverse and complex application scenarios. However, the performance of flexible electronic devices is limited by factors such as flexible substrates, material selection, and preparation processes. In particular, the conductivity, optoelectronic properties, and long-term stability of semiconductor films remain bottlenecks in improving the performance of flexible electronic devices. Therefore, finding a material that can provide high conductivity and optoelectronic properties while adapting to the requirements of flexible substrates is a key issue in the current flexible electronics field.
[0097] The goal of this embodiment is to apply the nanomaterial-based semiconductor thin film preparation method of the present invention to improve the conductivity, optoelectronic properties, mechanical flexibility and long-term stability of flexible electronic devices by optimizing the performance of the thin film material, thereby promoting the development of flexible electronic device technology.
[0098] Step S1: Preparation and mixing of nanomaterials In this example, we selected graphene, MoS2 (transition metal dichalcogenides), and quantum dots (such as PbS and CdSe) as the base materials. Graphene provides high conductivity, MoS2 can adjust the band gap and enhance optoelectronic properties, and the addition of quantum dots can extend the film's optical response range, particularly from the ultraviolet to the visible range.
[0099] The composite solution is prepared with a mass fraction of 20%-30% graphene, 30%-40% MoS2, and 5%-15% quantum dots. NMP and DMF are used as solvents, with a concentration of 4-6% by weight. Ultrasonic dispersing is used to ensure uniform dispersion of the nanomaterials throughout the solution.
[0100] Step S2: Thin film coating The prepared composite solution is then coated onto a flexible substrate. The substrate is a flexible polyester film (PET film) coated with a transparent conductive oxide (TCO). First, the substrate is cleaned to remove surface impurities and enhance film adhesion. In this example, spin coating is performed at a speed of 2000 rpm and a time of 60 seconds, with a film thickness controlled between 150 and 250 nm. By controlling the spin coating rate and solution concentration, the uniformity and quality of the film are effectively controlled.
[0101] Step S3: Electric field modulation After coating, the film enters the electric field modulation step. The purpose of electric field modulation is to optimize the electron migration path within the film and improve its conductivity. By applying an electric field, electrons in the film migrate more efficiently, reducing carrier recombination and interfacial losses. The applied electric field intensity is set to 3 V / cm, and the electric field modulation time is 20 minutes.
[0102] While applying an electric field, the film is kept at 60°C, a temperature that helps accelerate electron migration and improve electron mobility. This electric field modulation process not only enhances the film's conductivity but also reduces carrier recombination within the film, improving the performance of flexible electronic devices.
[0103] Step S4: Annealing After electric field modulation, the film entered the annealing stage. The annealing temperature was set at 320°C for 30 minutes under a nitrogen atmosphere at a flow rate of 50 mL / min. The purpose of annealing was to further optimize the film's microstructure, reduce lattice defects, and enhance its conductivity and photoelectric properties. After annealing, the film's lattice structure became more stable, significantly improving its conductivity and photoelectric conversion efficiency.
[0104] Step S5: Surface modification and functionalization After annealing, the film enters the surface modification and functionalization step. During this stage, the film surface is modified by immersing it in a functionalization solution. The film surface is functionalized using a solution containing amino (–NH2) and carboxyl (–COOH) groups. These groups enhance the film's surface hydrophilicity, improving adhesion to the substrate and ultimately enhancing the film's stability and mechanical properties.
[0105] At the same time, self-assembled monolayer (SAM) technology is used to form a monolayer on the film surface to further enhance the interfacial stability of the film surface. Through these modification treatments, the photoelectric responsiveness of the film surface is significantly improved, enhancing the long-term stability and working efficiency of the film in optoelectronic devices.
[0106] Assembly of flexible electronic devices After surface functionalization, the film is then used in flexible electronic devices. In this example, a nanomaterial-based semiconductor film is used as the electrode material for a flexible optoelectronic device. First, electrode materials (such as gold or silver) are deposited on the film surface by evaporation or sputtering to form the positive and negative electrodes of the flexible electronic device. Finally, the assembled flexible electronic device is subjected to performance testing to verify its optoelectronic responsiveness and stability.
[0107] Table 1. Comparison table of experimental data of examples Example 2 (photodetector) showed the highest electron mobility (120cm 2 / V·s) and photoelectric conversion efficiency (22%), making it suitable for applications in high-efficiency photodetection. Its fast response speed allows it to quickly respond to optical signals, but its relatively low mechanical stability (4%) makes it unsuitable for use in environments with high mechanical strain.
[0108] Example 1 (solar cell) achieved the best long-term stability, reaching 95%, and had a good photoelectric conversion efficiency (18%). This thin film material is suitable for use in solar cells and remains stable over long periods of use, but its mechanical stability is poor (5%), making it unsuitable for applications requiring high flexibility.
[0109] Example 3 (flexible electronic device) demonstrates excellent mechanical stability and a stretchability of 7%, making it well-suited for bendable and wearable electronic devices. While its photoelectric conversion efficiency of 20% is slightly lower than that of the other examples, it still offers good performance and is suitable for flexible electronic applications.
[0110] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a semiconductor thin film based on nanomaterials, characterized in that: The following steps are involved: Step 1: preparing graphene, transition metal disulfide material and quantum dots, and mixing them in a predetermined ratio to form a composite solution; Step 2: coating the composite solution onto a substrate to form a thin film by spin coating, spray coating or dip coating; Step 3: Applying an external electric field to the coated film for modulation to optimize the electron migration path; Step 4: performing low temperature annealing treatment; Step 5: Obtain a semiconductor film with high electron mobility and good photoelectric conversion performance.
2. The method for preparing a semiconductor thin film based on nanomaterials according to claim 1, characterized in that: The components in the composite solution are mixed in the following weight proportions: 10%-30% graphene, 20%-40% MoS2, 5%-15% quantum dots, 20%-50% alumina, 1%-10% organic solvent, and 0.5%-2% interface modifier.
3. The method for preparing a semiconductor thin film based on nanomaterials according to claim 1, characterized in that: The quantum dots are CdSe, PbS or a mixture thereof, and the particle size of the quantum dots is in the range of 3-10 nm.
4. The method for preparing a semiconductor thin film based on nanomaterials according to claim 1, characterized in that: The substrate is an aluminum oxide substrate, the thickness of the thin film deposition is 50-500 nm, and the surface of the substrate is plasma treated.
5. The method for preparing a semiconductor thin film based on nanomaterials according to claim 1, characterized in that: The spin coating method has a spin coating rate of 1500-3000 rpm, a spin coating time of 30-60 seconds, and an ambient temperature during the coating process of 20-25°C.
6. The method for preparing a semiconductor thin film based on nanomaterials according to claim 1, characterized in that: The electric field modulation step includes applying an electric field with an electric field strength of 1-10 V / cm, and the electric field modulation time is 5-30 minutes.
7. The method for preparing a semiconductor thin film based on nanomaterials according to claim 1, characterized in that: The annealing temperature is 250-400°C, the annealing time is 30-60 minutes, and the atmosphere during the annealing process is nitrogen protection.
8. The method for preparing a semiconductor thin film based on nanomaterials according to claim 1, characterized in that: The thin film coated on the substrate is deposited by spraying, with a spraying distance of 15-30 cm, a spraying speed of 1-5 m / s, and a spraying thickness controlled at 50-500 nm.
9. The method for preparing a semiconductor thin film based on nanomaterials according to claim 1, characterized in that: The graphene in the composite solution is synthesized by chemical vapor deposition or reduced graphene oxide method, MoS2 is synthesized by CVD method, and quantum dots are synthesized by solution method. The particle size can be controlled by adjusting the solvent, temperature and reaction time.
10. The method for preparing a semiconductor thin film based on nanomaterials according to claim 1, characterized in that: The electric field modulation step is performed by an electric field assisted deposition device, the electric field intensity range is 1-10 V / cm, the electric field application time is 5-30 minutes, and the electric field direction is parallel to the film deposition direction.